Multivocal Literature Review on User Story Models for COSMIC Sizing - Ecar, Miguel; da Silva, João Pablo (Anais da Escola Regional de Engenharia de Software (ERES), 2017)
User Story is a technique widely used in Agile development. It is characterized as short and high level description of required functionality, written in customer language during very early stage of requirement gathering. COSMIC method is a second generation technique of function size measurement. The requirement estimation precision in COSMIC is directly proportional to requirement detailing level. The current user story writing models may have lacks of important information for COSMIC measurement purposes. Considering this, the paper presents a multivocal literature review which presents current user story models found in traditional and gray literature. Furthermore, we analyze the effectiveness of this models for COSMIC sizing purposes.